Isotopic effects in mechanistic studies of biotransformations of fluorine derivatives of L-alanine catalysed by L-alanine dehydrogenase. (May 2017) - Szymańska-Majchrzak, Jolanta; Pałka, Katarzyna; Kańska, Marianna
Abstract: Synthesis of 3-fluoro-[2- 2 H]-L -alanine (3-F-[ 2 H]-L -Ala) in reductive amination of 3-fluoropyruvic acid catalysed byL -alanine dehydrogenase (AlaDH) was described. Fluorine derivative was used to study oxidative deamination catalysed by AlaDH applied kinetic (for 3-F-L -Ala in H2 O - KIE's on Vmax : 1.1; on Vmax /KM : 1.2; for 3-F-L -Ala in 2 H2 O – on Vmax : 1.4; on Vmax /KM : 2.1) and solvent isotope effect methods (for 3-F-L -Ala - SIE's on Vmax : 1.0; on Vmax /KM : 0.87; for 3-F-[2- 2 H]-L -Ala – on Vmax : 1.4; on Vmax /KM : 1.5). Studies explain some details of reaction mechanism. Highlights: Synthesis of 3-fluoro-[2- 2 H]-L-alanine was performed. The reactions were catalysed using the enzyme L-alanine dehydrogenase. Performed reactions involved fluorinated analogues of L-alanine. Solvent isotope effects of deuterium were determined. Kinetic isotope effects were determined for obtained 3-fluoro-L-alanine. The mechanism of reaction catalysed by L-alanine dehydrogenase was proposed.